Funcionalização em sítios distintos da molécula do óxido de limoneno: processos “one-pot” de hidroformilação/isomerização e de hidroformilação/acetilação - Mileny Pires de Oliveira (2021)
Using rhodium-based catalytic systems, one-pot processes of hydroformylation/ isomerization and hydroformylation/acetylation of limonene oxide were developed, in order to produce value-added products via the functionalization of the original molecule at different reactive sites. Limonene oxide is naturally found in citrus essential oils and can be produced from the epoxidation of limonene, a terpenic compound widely available in nature. The oxirane ring present in the structure of this substrate makes it extremely sensitive to isomeric rearrangements with opening of the oxirane ring. Initially, the hydroformylation of this substrate was studied, using a CO/H2 mixture (syngas) and rhodium catalytic precursor in combination with auxiliary phosphorus ligands. Only one aldehyde was obtained from the regioselective hydroformylation of the terminal double bond in the substrate molecule, reaching selectivity values greater than 80% under optimized conditions. The hydroformylation of limonene oxide demonstrated good performance also in green solvents, especially in dimethylcarbonate (DMC) and ethanol, in which the formation of acetals was not observed. In the one-pot process, which, in addition to hydroformylation, involves the previous isomerization of the substrate, a silica-supported heteropolyacid (20% H3PW12O40/SiO2) was used as the catalyst for the isomerization step. The first step of the process resulted in the formation of three major products, which were then hydroformylated, generating three main aldehydes. The main final product in most experiments was the aldehyde originated from dihydrocarvone, which was obtained in 70% yield in the green solvent DMC. Combined selectivity for aldehydes of about 90% in DMC and diethylcarbonate (DEC) solutions was obtained, demonstrating a superior performance of these solvents as compared to toluene. In the one-pot process that involves cleavage/acetylation of the oxirane ring present in the substrate structure, after its hydroformylation, acetic anhydride (Ac2O) or acetic acid (HOAc) were used as acetylating agents. Three major products were obtained: mono- and di-acetates of the aldehyde formed by the hydroformylation of the original substrate. Ac2O showed higher efficiency as an acetylating agent and the ability to undergo hydrogenolysis under hydroformylation conditions, generating HOAc. The formation of monoacetates followed the Fürst-Plattner rule of trans-diaxial opening of the substrate oxirane ring. Total selectivity for acetates of about 80% was obtained. It has been shown that, in this process, green solvents such as anisole, DMC and DEC are good alternatives to replace the conventional toluene solvent. The development of the one-pot processes mentioned in this work enabled the synthesis of polyfunctional products, with most of them being novel compounds, as far as we know. All aldehydes obtained have a pleasant aroma and can therefore be used in the formulation of cosmetics and perfumes, even directly as a mixture, without the separation of individual compounds.